2018
DOI: 10.1021/acs.macromol.8b00851
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Polyfarnesene

Abstract: This paper represents the first comprehensive report of the molecular weight dependence of the dynamics of polyfarnesene (PF), utilizing oscillatory shear rheology and broadband dielectric spectroscopy. Extended PF chain conformations arising from tightly packed C11/C13 pendant groups reduce the probability of chain entanglements and lead to Rouse-like melt dynamics up to a critical molecular weight ∼105 g/mol. At higher molecular weights, PF behaves as an entangled polymer melt. Dielectric spectroscopy measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 32 publications
1
58
1
5
Order By: Relevance
“…Furthermore, it has been shown that poly(Myr) polymerized with predominantly 1,4‐addition had a T g of −68°C compared to a T g of −54°C after hydrogenation 60 . T g of poly(Far) in this study was also not observed in DSC but it is reported to be −73°C 34 . Similarly, T g s of the hydrogenated poly(Far) also increased compared to the unsaturated analog.…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…Furthermore, it has been shown that poly(Myr) polymerized with predominantly 1,4‐addition had a T g of −68°C compared to a T g of −54°C after hydrogenation 60 . T g of poly(Far) in this study was also not observed in DSC but it is reported to be −73°C 34 . Similarly, T g s of the hydrogenated poly(Far) also increased compared to the unsaturated analog.…”
Section: Resultscontrasting
confidence: 41%
“…Indeed, a poly(Myr) repeating unit contains two double bonds and a poly(Far) repeating unit has three double bonds as shown in Scheme 1. As a result, the entanglement molecular weights ( M e ) of poly(Myr) and poly(Far) are much greater than poly(BD) and poly(IP) (i.e., M e,Myr = 18,000–25,000 g/mol and M e,Far = 50,000 g/mol versus M e,BD = 1500–1900 g/mol and M e,IP = 3000–5000 g/mol, where M e depends on composition of cis and trans or 1,2‐ and 1,4‐addition repeating units) 33,34 . Therefore, the hydrogenation of poly(Myr) and poly(Far) is beneficial in order to lower their M e s and have comparable viscoelastic properties without achieving high molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…1 The presence of a hemiterpene unit makes feasible the polymerization of most terpenes, including the non-conventional ones such as b-myrcene, trans-b-farnesene, and b-ocimene, which could potentially yield polymers with similar rubbery features to polybutadiene (PB) and polyisoprene (PI). [2][3][4] Although b-myrcene and b-farnesene have readily proved their capacity to be polymerized, [4][5][6] the synthesis of these polyterpenes with high performance, require control in their microstructure, which can be achieved via coordination polymerization. In this context, neodymium (Nd)-based catalytic system has demonstrated to give excellent results, yielding polydienes with a high content of cis-1,4 microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the 3,4- and 1,2-units in the side chain is increasingly overcompensated by the long side chains, corresponding to a more bottlebrush-like structure . On the other hand, the bottlebrush-like structure of polyfarnesene causes a significantly higher entanglement molecular weight ( M e (PFar) = 50 kg mol –1 ) in comparison to polymyrcene ( M e (PMyr) = 18 kg mol –1 ) and polyisoprene ( M e (PI) = 5.4 kg mol –1 ), which is attributed to the increased persistence length of polyfarnesene . The decrease in entanglement molecular weight follows the trend of decreasing side chain length, in the order PFar > PMyr > PI.…”
Section: Anionic Polymerization Of Terpenesmentioning
confidence: 99%
“…The decrease in entanglement molecular weight follows the trend of decreasing side chain length, in the order PFar > PMyr > PI. In a seminal work, Runt et al studied in detail the influence of the bottlebrush-like structure of polyfarnesene on its molecular dynamics . Below the critical molecular weight ( M c (PFar) = 100 kg mol –1 ) polyfarnesene behaves like a bottlebrush-like polymer and exhibits Rouse-like melt dynamics.…”
Section: Anionic Polymerization Of Terpenesmentioning
confidence: 99%